Cephalic muscle development in the Australian lungfish, Neoceratodus forsteri - Ziermann, Janine M; Clement, Alice M; Ericsson, Rolf; Olsson, Lennart (Journal of morphology, 2018)
Lungfishes are the extant sister group of tetrapods. As such, they are important for the study of evolutionary processes involved in the water to land transition of vertebrates. The evolution of a true neck, that is, the complete separation of the pectoral girdle from the cranium, is one of the most intriguing morphological transitions known among vertebrates. Other salient changes involve new adaptations for terrestrial feeding, which involves both the cranium and its associated musculature. Historically, the cranium has been extensively investigated, but the development of the cranial muscles much less so. Here, we present a detailed study of cephalic muscle development in the Australian lungfish, Neoceratodus forsteri, which is considered to be the sister taxon to all other extant lungfishes. Neoceratodus shows several developmental patterns previously described in other taxa; the tendency of muscles to develop from anterior to posterior, from their region of origin toward insertion, and from lateral to ventral/medial (outside-in), at least in the branchial arches. The m.protractor pectoralis appears to develop as an extension of the most posterior m.levatores arcuum branchialium, supporting the hypothesis that the m.cucullaris and its derivatives (protractor pectoralis, levatores arcuum branchialium) are branchial muscles. We present a new hypothesis regarding the homology of the ventral branchial arch muscles (subarcualis recti and obliqui, transversi ventrales) in lungfishes and amphibians. Moreover, the morphology and development of the cephalic muscles confirms that extant lungfishes are neotenic and have been strongly influenced via paedomorphosis during their evolutionary history.
Keywords: Dipnoi; Skull; Muscle Development; cranial muscles; ontogeny; Muscles; vývoj svalů; lebka; Austrálie; zvířata; Neck; krk; svaly; neoteny; Australia; paedomorphosis; Fishes; ryby; heterochrony; Animals